Working with trans survivors of sexual violence : a guide for professionals - Rymer, Sally; Cartei, Valentina (London : Jessica Kingsley Publishers, 2019)
This book provides practical advice for professionals working with transgender (including non-binary) people who have survived any form of sexual violence or abuse. It gives professionals an understanding of the impact and trauma of sexual violence on trans people, as well as the additional difficulties they face accessing services that have traditionally been designed to serve cisgendered clients. The authors reveal specific issues faced by trans people as they recover from traumatic sexual experiences, and what steps professionals and organisations can take to meet the needs of the trans community. They also take a critical look at what can be done to reduce discrimination and how to mitigate the traumatic effects of sexual violence on trans individuals, by recommending effective responses to all levels of service delivery, from organisational policies to advice for front-line professionals.
Introduction -- Introduction to trans identities -- Violence experienced by the trans community -- Trauma and its effects -- Problems with accessing mainstream services -- Best practice-organisations -- Best practice-individual practitioners -- Looking ahead.
Print version record.
Includes bibliographical references (pages 159-171) and indexes.
eBooks on EBSCOhost
Keywords: Social work with transgender people; Social work with sexual minorities; Sexual abuse victims -- Services for; Transgender people -- Crimes against; Transgender people -- Services for; Sex crimes; Adult child abuse victims; Victims; Transgender people; Anti-transgender violence; Hate crimes; LGBTQ+ victims of hate crimes; LGBTQ+ health care centers; Sex Offenses; Health Services for Transgender Persons; Transgender Persons; Sexual and Gender Minorities; Adult Survivors of Child Abuse; Survivors; Service social aux transgenres; Service social aux minorités sexuelles; Victimes d'abus sexuels -- Services; Transgenres -- Crimes contre; Transgenres -- Services; Violence sexuelle; Enfants maltraités devenus adultes; Victimes; Victims; Sex crimes; Adult child abuse victims; Social work with transgender people; Sexual abuse victims -- Services for; Social work with sexual minorities; Electronic books